2007
DOI: 10.1007/s10750-007-9083-4
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among recent Alpine Cladocera remains and their environment: implications for climate-change studies

Abstract: Our objective was to assess the potential of Cladocera from mountain lakes for climate reconstruction. We related Cladocera from surface sediments of Alpine lakes (1,502-2,309 m asl) to 29 abiotic environmental variables using statistical methods. The environmental dataset included water chemistry, lake depth, and bi-hourly water-temperature logs, which were used to assess mean monthly water temperatures, dates of freezing and breakup, spring and autumn mixing. We found 14 different Cladocera of the families B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
59
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 69 publications
7
59
1
Order By: Relevance
“…It is not surprising that such taxa persisted in the YD, because these species are known to occur over a wide range of conditions, and they are tolerant of environmental stress (Duigan & Birks, 2000); they are also common in northern and in European mountain lakes (Kamenik et al, 2007;Bjerring et al, 2009). These species were often found to be pioneer taxa, i.e., early immigrants following the retreat of the ice (Szeroczyńska, 1998a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is not surprising that such taxa persisted in the YD, because these species are known to occur over a wide range of conditions, and they are tolerant of environmental stress (Duigan & Birks, 2000); they are also common in northern and in European mountain lakes (Kamenik et al, 2007;Bjerring et al, 2009). These species were often found to be pioneer taxa, i.e., early immigrants following the retreat of the ice (Szeroczyńska, 1998a).…”
Section: Discussionmentioning
confidence: 99%
“…This seems to imply that Cladocera records derived from floodplain sediments can be used to reconstruct changes in temperature just as reliably as can records based on cladoceran assemblages from lakes unaffected by fluvial influence. Recent ecological studies also suggest that Cladocera do respond to climate change (Kamenik et al, 2007;Bjerring et al, 2009;Nevalainen et al, 2011) even over a few decades, while their response to temperature is complex and indirect (Kattel et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these conditions, cladocerans become important as indicator species and for understanding the long-term ecological change of these lakes (Frey, 1986;Alric et al, 2013). Furthermore, the generally good preservation of their remains in lake sediment after death, the associated record of diversity of subfossil cladoceran assemblages, has allowed the reconstruction of long-term environmental forcing in high altitude lakes around the world (Lotter et al, 1997(Lotter et al, , 1998Kamenik et al, 2007;Kattel et al, 2008;Alric & Perga, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…pollen). Also correlations between Cladocera frequency and climatic conditions have been previously studied (Lotter et al, 1997;Szeroczyńska, 2006Kamenik et al, 2007. The initial interpretive possibilities for palaeoecological studies of Cladocera in flood records have been recently demonstrated, and tested mostly with young sediment (from the last two hundred years) associated with human activity (Galbarczyk-Gąsiorowska et al, 2009).…”
Section: Introductionmentioning
confidence: 99%